Broad antibiosis activity of Bacillus velezensis and Bacillus subtilis is accounted for by a conserved capacity for lipopeptide biosynthesis - Alam, Jahangir; Olofintila, Oluwakemisola E.; Moen, Francesco S.; Noel, Zachary A.; Liles, Mark R.; Goodwin, Douglas C. (Frontiers in Microbiology, 2025)
We evaluated 284 strains from 15 species across five genera in the Phylum Bacillota (Bacillus, Priestia, Cytobacillus, Neobacillus, and Gottfriedia) for antibiosis activity against the pathogenic oomycete, Phytophthora nicotianae. Fifty-eight strains were strong inhibitors, while 41 and 185 were weak and noninhibitors, respectively. Only Bacillus strains were strong inhibitors, and inhibitory metabolites were most frequently (55 of 58 strains) expressed from five species (B. pumilus, B. safensis, B. altitudinis, B. velezensis, and B. subtilis). Strongly inhibitory strains from B. velezensis (all) and B. subtilis (all but one) were also strong inhibitors of the fungal pathogens Fusarium oxysporum, Fusarium graminearum, and Rhizoctonia solani; therefore, these Bacillus strains were designated as generalists. The strong P. nicotianae inhibitors from B. pumilus, B. safensis, and B. altitudinis strains only weakly inhibited R. solani and did not inhibit F. oxysporum or F. graminearum; therefore, these strains were designated as Oomycete specialists. Lipopeptide-encoding biosynthetic gene clusters (BGCs) were prominently represented within the five bioactive generalist species and virtually absent from the 10 non-inhibitory species. Surfactin-encoding BGCs were observed across all specialists and generalists. B. subtilis strains also carried a fengycin BGC, and some B. velezensis strains were found to encode a novel iturin and fengycin BGC. Iturin (including bacillomycin L), fengycin, and surfactin were the most commonly observed lipopeptide BGCs among the most bioactive species, and many strains contained all three. Lipopeptides from strongly inhibitory B. velezensis JJ334 were isolated, identified, and characterized by LC-MS. Fengycin and bacillomycin L produced strong inhibition of oomycetes and fungi as compared to surfactin. Fengycin was the strongest inhibitor among lipopeptides evaluated. Six to thirteen derivatives of each lipopeptide were observed, varying primarily in fatty acid chain length.